Where am I Now: Symbols Used in Manggarai Funeral Rite, Indonesia - Hieronimus Canggung Darong; Erna Mena Niman; Stanislaus Guna (Changing Societies & Personalities, 2023)
A symbol has a specific meaning and represents the user’s conception, way of thinking, and interpretation. This study aimed to analyze the symbolic interactions of the Manggarai ethnic funeral rite. Data were collected through observation, interviews, and documents. The results of the analysis showed that the symbols are employed as a spiritual and social tool to aid understanding of the outside world as well as to describe and learn the transcendent secret world, such as the “truth of being”. Therefore, the symbols used reflect the interpersonal relations with others, ancestors, and God, called socio-theological relations, and profound philosophy of existence, as they are extremely vulnerable and totally reliant on their predecessors and God.